Fair trial rights of the accused : a documentary history - Banaszak, Ronald A. (Primary documents in American history and contemporary issues., 2002)
This collection of over 60 primary documents traces the evolution of trial rights from English and colonial beginnings to our contemporary understanding of their meaning. Court cases and other documents bring to life the controversies that have historically surrounded the rights of those who have been accused in the American legal system. Explanatory introductions to documents aid users in understanding the various arguments put forth and the context in which the document was written, while illuminating the significance of each document.